Surveillance of post-caesarean surgical site infections in a hospital with limited resources, Cambodia - Sok Srun; Yin Sinath; An Thoun Seng; Meas Chea; Mony Borin; Somary Nhem; Amanda Daniel; Nora Chea; Nima Asgari; Anne Rachline; Za Reed; Rodney Hoff; et al. (Journal of Infection in Developing Countries)
Introduction: In Cambodia, we implemented a pilot surveillance of superficial surgical site infections (SSSI) following caesarean deliveries (CD) in a provincial hospital, to estimate their incidence, describe their clinical management, and determine their causative pathogens.